Answer:
k= -9
Step-by-step explanation:
2k-3=9k+63-3 [expand the 9(k+7) first]
2k-9k=63-3+3 [put the like terms together]
-7k=63 [do the simple math]
k= 63 ÷ by -7
k=-9
f(x) = (3/4)ˣ - 4
As x gets really negative (3/4)ˣ grows positively without bound (because it's (4/3)⁻ˣ and 4/3 > 1).
As x gets really positive (3/4)ˣ tends to zero but never quite gets there.
So (3/4)ˣ > 0 for all x
So f(x) > 0 - 4 for all x
Answer: { y | y > -4 }, first choice
Answer: 72
Step-by-step explanation: volume of a pyramid = v= lwh/3
v= 6*6*6/3
v = 216/3
v = 72
Answer:
B
Step-by-step explanation:
i gottt youu
Take it and divide it by 5, or you can multiply it by .2